2005
DOI: 10.1111/j.1365-2230.2005.01729.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous sarcoidosis in Asians: a report of 25 patients from Singapore

Abstract: Sarcoidosis is a systemic noncaseating granulomatous disorder of unknown origin involving multiple organ systems. There has been no report so far to describe the epidemiological pattern of cutaneous involvement in sarcoidosis in South-East Asia with diverse ethnic groups. A retrospective study examining the clinicopathological features of all patients diagnosed with sarcoidosis at a tertiary dermatology centre in Singapore from 1980 to 2003 was conducted. Cutaneous sarcoidosis was diagnosed in 25 patients: 13 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 8 publications
2
30
1
4
Order By: Relevance
“…2,7 The involvement of the skin occurs in 25% of the cases and it can develop in any phase of the disease although it is more common at the beginning 8 .…”
Section: Discussionmentioning
confidence: 99%
“…2,7 The involvement of the skin occurs in 25% of the cases and it can develop in any phase of the disease although it is more common at the beginning 8 .…”
Section: Discussionmentioning
confidence: 99%
“…In 2 studies in Singaporean Asian and Black South African sarcoidosis patients ( n = 55), 3.33–4% of patients had AA while 10–32% had sarcoid-associated pulmonary disease [6, 7]. Evans syndrome (ES) is a rare hematological manifestation of autoimmune hemolytic anemia or immune thrombocytopenia in the presence of SLE.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, 9 studies (5 case-control and 4 cross-sectional) stratified patients based on the type of atopic respiratory disease (i.e., AR vs. asthma), and 7 studies (1 case-control and 6 cross-sectional) reported hair loss in patients with systemic disease with pulmonary manifestations (e.g., sarcoidosis [6, 7], mixed connective tissue disease [MCTD] [8], dermatomyositis [DM] [9], SLE [10, 11], and emphysema) [12]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three patients relapsed within 3 months of apremilast discontinuation. 169 Anecdotal reports documenting improvement of cutaneous sarcoidosis with isotretinoin 189,190 and with allopurinol have been published. 191 Case reports have described improvement of steroidrefractory lung function during cyclosporine therapy but a randomized trial found no benefit as a steroid-sparing agent and increased complications.…”
Section: Other Pharmacologic Agentsmentioning
confidence: 97%